Analysis of Student Satisfaction with University Management Services - Suherman, Agus; Inoe, Hiromu (Jurnal Pendidikan Progresif, 2025)
Analysis of Student Satisfaction with University Management Services. Introduction: This study aimed to determine and measure student satisfaction with the quality of services at Syekh-Yusuf Islamic University, adapting a service quality model by incorporating an additional dimension, "Information Systems." Furthermore, the research compared satisfaction levels based on demographic factors such as age, gender, employment status, marital status, study program, and year of entry. Objectives: This study aimed to determine and measure student satisfaction with the quality of services at Syekh-Yusuf Islamic University and to compare satisfaction levels based on age, gender, employment status, marital status, study program, and year of entry. Methods: A descriptive quantitative research design with a cross-sectional survey approach was employed. Data were collected from 576 students at Syekh-Yusuf Islamic University using a 30-item service satisfaction instrument across six dimensions (tangibles, responsiveness, reliability, assurance, empathy, and information systems) with a Likert scale of 1-5. Instrument validity was tested using Pearson correlation and reliability with Cronbach's alpha. Data analysis involved descriptive statistics, the Kolmogorov-Smirnov test for normality, and non-parametric tests (Mann-Whitney and Kruskal-Wallis) for mean differences due to non-normal distribution in certain demographic groups. Findings: Overall student satisfaction with UNIS services was 3.88 out of 5 (77.63% satisfaction). Tangibles received the highest satisfaction, while responsiveness was the lowest. Significant differences were found based on age, faculty, and year of enrollment (p-value less than 0.05). However, no differences were found based on gender or parental income (p-value higher than 0.05). Conclusion: This study measures student satisfaction with services at Syekh-Yusuf Islamic University, adapting a service quality model by incorporating the "Information Systems" dimension. The research compares satisfaction across demographic factors such as age, gender, employment status, marital status, study program, and year of entry. Findings suggest that while student satisfaction is generally positive, improvements are needed, especially in responsiveness, to meet the university's strategic goals of providing consistent and high-quality services to all students. Keywords: higher education, service quality, student satisfaction, university services.